Emission of Greenhouse Gases in Afghanistan - Faqiri, Nasrin; Quraishi, Roya (Journal of Natural Sciences – Kabul University, 2023)
Afghanistan is one of the Asian countries in the emission of greenhouse gas production. However, this country is one of the most vulnerable countries in the world in front of climate change and in a specific way related to the vulnerability of drought, floods and landslides. This vulnerability is partly related to exposure to natural disasters. However, this vulnerability is the result of the high sensitivity of the Afghan population to natural disasters. Sensitivity has several dimensions and depends on socio-economic, cultural and political factors. There is not much expectation at least in the short to medium term to reduce the amount of greenhouse gases from Afghanistan. Because considering the poverty and relatively low level of development in the country, such an expectation is neither realistic nor fair. Regarding Afghanistan, the main challenge is to ensure that the increase in greenhouse gas emissions that goes along with the country's development will ultimately benefit the poor. Because it is the poor who are most vulnerable to the effects of climate change.